Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2001
DOI: 10.1038/88871
|View full text |Cite
|
Sign up to set email alerts
|

Telomere dysfunction and evolution of intestinal carcinoma in mice and humans

Abstract: Telomerase activation is a common feature of advanced human cancers and facilitates the malignant transformation of cultured human cells and in mice. These experimental observations are in accord with the presence of robust telomerase activity in more advanced stages of human colorectal carcinogenesis. However, the occurrence of colon carcinomas in telomerase RNA (Terc)-null, p53-mutant mice has revealed complex interactions between telomere dynamics, checkpoint responses and carcinogenesis. We therefore sough… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
352
1
5

Year Published

2002
2002
2012
2012

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(386 citation statements)
references
References 28 publications
22
352
1
5
Order By: Relevance
“…As anaphase bridge index (ABI) has been reported to correlate with the extent of CIN (Gisselsson et al, 2000), it has been used as a marker of CIN (Gisselsson et al, 2000;Rudolph et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As anaphase bridge index (ABI) has been reported to correlate with the extent of CIN (Gisselsson et al, 2000), it has been used as a marker of CIN (Gisselsson et al, 2000;Rudolph et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, it has been argued that published data provide little evidence for CIN in early colorectal tumors (Sieber et al, 2003). In later stages, chromosomal aberrations and LOH are more frequently observed, and ABI is increased (Rudolph et al, 2001). However, the confusion may have been caused partly by the assumption that CIN is a clear qualitative phenotype derived from a unified mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Cases 1 and 3 were both classified as benign PA, but exhibited a high frequency of anaphase bridges. Investigations of colorectal polyps in mice have shown that BFB events may actually occur already at the dysplastic stage (Rudolph et al, 2001). In man, mitotically unstable ring chromosomes, telomeric associations and anaphase bridges are common in borderline malignant mesenchymal tumours, including giant cell tumours of bone and atypical lipomatous tumours (Mandahl et al, 1998;Gisselsson et al, 1999).…”
Section: Molecular and Cellular Pathologymentioning
confidence: 99%
“…1-5) [3][4][5][6][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] . This method is now also used to measure NPBs, a biomarker of dicentric chromosomes resulting from telomere end-fusions or DNA misrepair, and to measure NBUDs, a biomarker of gene amplification [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] . The significance of these developments and the concept of the CBMN assay as a ''cytome'' assay of chromosomal instability are explained in the following sections.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative mechanism for dicentric chromosome and NPB formation is telomere end fusion caused by telomere shortening, loss of telomere capping proteins or defects in telomere cohesion 40 , but in this case the NPB is not necessarily accompanied by an acentric chromosome fragment or an MN. The formation of anaphase bridges and NPBs has been observed in models of rodent and human intestinal cancer in vivo and shown to correlate with telomere length, indicating that NPB formation may also be used as a surrogate measure of critically short telomeres 25 . Real-time in vitro studies showed that anaphase bridges may be broken in more than one region during late anaphase, leading to the formation of acentric chromosome fragments and eventually MNi 26,27 .…”
Section: Introductionmentioning
confidence: 99%